Reestructuración de la arquitectura de software para la implementación de software como servicio (SaS) en la empresa Gearsis S.A.S. (2020)
Companies need the software systems that support their operation, and the proper functioning of these depend in part on the software architectures that they implement. The architecture of a software system is designed to meet the functional and non-functional requirements established by those interested in the system such as: users, customers, suppliers. In addition, the software architecture directly impacts the way in which these products are marketed, allowing business models to be applied which improve the competitiveness of said products. A well designed architecture is key for software companies to evolve with the dynamism demanded by today's economies.